Neuropsychological Functioning in Older Adults with Obesity: Implications for Bariatric Surgery - Roth, Robert M. (J Nutr Gerontol Geriatr, 2019)
Bariatric surgery is the most effective approach to treating morbid obesity, resulting in decreased morbidity, mortality, and improved quality of life. Research on outcomes has generally been restricted to young and middle-aged adults, despite a growing epidemic of obesity in older adults. The use of bariatric surgery has been limited in older individuals, in part due to concerns that pre-existing cognitive dysfunction increases the risk of poor post-surgical outcomes, including cognitive decline. The literature on the relationship between obesity and cognition in older adults is emerging, but fraught by several methodological limitations. While there is insufficient research to determine the nature of cognitive outcomes following bariatric surgery in older adults, the aim of this paper is to review the existing evidence and make the case for further study.